Epilepsy and attention-deficit hyperactivity disorder: links, risks, and challenges - Williams A; Giust J; Kronenberger W; Dunn D (Neuropsychiatric Disease and Treatment, 2016)
Amy E Williams, Julianne M Giust, William G Kronenberger, David W DunnDepartment of Psychiatry, Riley Child and Adolescent Psychiatry Clinic, Indiana University School of Medicine, Indiana University Health Physicians, Indianapolis, IN, USAAbstract: Attention-deficit hyperactivity disorder (ADHD) has a prevalence rate of 7%–9% in the general population of children. However, in children with epilepsy, ADHD has been found to be present in 20%–50% of patients. This paper provides a review of ADHD prevalence in pediatric epilepsy populations and reviews data on specific symptom presentation and attention deficits in patients with epilepsy. This paper also reviews evidence-based treatments for ADHD and specifically the treatment of ADHD as a comorbid condition in children with epilepsy.Keywords: ADHD, epilepsy, seizure disorder, children